Reabilitação pulmonar no Brasil: percepções, práticas, barreiras e conhecimento dos profissionais de saúde - Mateus, Adriano Petrolini (Universidade Federal de São Carlos, 2024)
Chronic respiratory diseases (CRD) commonly occur with intolerance to physical exercise, deconditioning and reduced quality of life, with pulmonary rehabilitation (PR) being a therapeutic strategy proven to be beneficial for these patients. Despite consistent evidence, in practice, PR still needs improvements in implementation, access and quality of services. Therefore, to optimize PR delivery strategies, it is crucial to know the local context, guidelines for rehabilitation, and understanding about the dynamics of professionals working in PR. Objective: This study aims to characterize health care professionals as well as their knowledge regarding assistance to people with CRD, contrast knowledge about models and essential components with availability of those items in services and identify barriers to referring patients to PR services. Methods: From July to December 2023, an online survey was disseminated to healthcare professionals with experience in caring for CRD in PR. A questionnaire consisting of 58 questions (identification, components, models, knowledge and barriers to PR) was prepared and allocated to REDCap®. Results: The participating health professionals (n=60) were predominantly physiotherapists (n=54). PR Home based was the most well-known PR model (88.3%). The Brazilian Unified Health System (Sistema Únicod e Saúde - SUS) was the main financier of services (55.0%). Less knowledge about the models was associated with professionals who reported working in the SUS (p=0.01, Phi=0.31). Compliance with all minimum requirements was associated with PR funded by public educational institutions (p=0.03, Phi=0.31). Among the known benefits of PR, improving exercise capacity showed the highest agreement (95.0%) among participants. The lack of specialized centres (96.7%) was the factor identified as the biggest barrier to referring patients to PR. Conclusions: Physiotherapists represent the professional category that receives the most patients referred with CRD. The places where they work have the minimum resources necessary for PR. Knowledge about PR models and components exceeds their availability in professional practice, with participants demonstrating a good level of knowledge about the benefits of PR. In this study, reduced mobility due to dyspnoea and fatigue were presented as the main reasons for referring patients to PR programs, while the lack of specialized centres and patients' lack of knowledge of the benefits of PR stood out as barriers.
Pulmonary rehabilitation in Brazil: perceptions, practices, barriers and knowledge of health care professionals
Keywords: Doenças respiratórias; Reabilitação; Equipe multiprofissional; Fisioterapia; Países em desenvolvimento; Brasil; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL